MODERN COMPLEMENTARY FOODS IN THE PREVENTION OF ALLERGIC DISEASES: PROSPECTIVE STUDY RESULTS - Т. E. Borovik; N. G. Zvonkova; О. L. Lukoyanova; Т. V. Bushueva; Т. N. Stepanova; V. А. Skvortsova; N. N. Semenova; Ye. K. Kutafina; Ye. L. Semikina; Ye. А. Kopyl’tsova; E. G. Gemdzhyan (Вопросы современной педиатрии, 2014)
Background: Rate allergenic properties of the complementary food line based on grains, fruits/vegetables and meat in the diet of infants (0–1 years old). Methods: The study included children aged 4–6 months with natural, mixed or artificial feeding, who had not received any complementary food before. The children were almost healthy or had a burdened allergic history. Complementary foods (porridge, vegetable puree, meat puree and fruit puree) were administered basing on an individual plan depending on age, nutritional status and nature of feces. Tolerability of products and dynamics of mass-height and laboratory parameters were evaluated. At the beginning and at the end of the study, capillary blood was taken to determine the content of hemoglobin in red blood cells (MCH), the equivalent of hemoglobin in reticulocytes (RetHe), iron, ferritin, prealbumin, and specific E class immunoglobulin (IgE) to the proteins in cow's and goat milk, apples, pears, prunes, zucchini, broccoli, cauliflower, rice, maize, buckwheat, turkey meat, and rabbit meat (quantitative allergy diagnostics using an express method). In addition, a scatological study was performed. Results: 60 healthy children received complementary foods based on grains, fruits/vegetables and meat on a step-by-step basis. The level of specific IgE to food allergens in all children under the study was within normal range (0–135 IU/ml) both initially and after the administration of all the complementary foods studied. Conclusion: The investigated complementary foods have a low sensitizing potential, including in children with a burdened allergic history. This allows us to describe them as hypoallergenic products.